2015
DOI: 10.1099/ijs.0.000338
|View full text |Cite
|
Sign up to set email alerts
|

Marinobacter halophilus sp. nov., a halophilic bacterium isolated from a salt lake

Abstract: A Gram-staining-negative bacterium, strain XCD-X12 T , was isolated from Xiaochaidan Lake, a salt lake (salinity 9.9 %, w/w) in Qaidam basin, Qinghai Province, China. Its taxonomic position was determined by using a polyphasic approach. Cells of strain XCD-X12T were nonspore-forming rods, 0.4-0.7 mm wide, 2.1-3.2 mm long and motile with a single polar flagellum. T was 34¡5 %. Based on these data, it is concluded that strain XCD-X12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…Similarly to the dune groundwater, gram-negative and aerobic microbes are prominent. Halophile ( Halobacteria ) have a more substantial presence in GW-2 (southern edge of the playa), implying higher salinity at this location (Jeong et al, 2013; Madigan et al, 2015; Zhong et al, 2015), which is confirmed by our conductivity measurements where GW-1 measured 59 μS and GW-2 139.9 μS (Table 1). The abundances of Thiomicrospira and Sediminimonas imply that both locations are primarily oxidizing environments with readily available reduced compounds (Wang et al, 2009; Madigan et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly to the dune groundwater, gram-negative and aerobic microbes are prominent. Halophile ( Halobacteria ) have a more substantial presence in GW-2 (southern edge of the playa), implying higher salinity at this location (Jeong et al, 2013; Madigan et al, 2015; Zhong et al, 2015), which is confirmed by our conductivity measurements where GW-1 measured 59 μS and GW-2 139.9 μS (Table 1). The abundances of Thiomicrospira and Sediminimonas imply that both locations are primarily oxidizing environments with readily available reduced compounds (Wang et al, 2009; Madigan et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Our research demonstrated that a few bacterial taxa namely Idiomarina , Psychroflexus , Roseovarius , and Marinobacter appeared over a wide salinity range, i.e., 4.5–27% showing their broad ecological plasticity. Indeed their representatives have been isolated from a variety of environments starting from estuaries and seawater to hypersaline crystallizer ponds (Lee et al 2015 ; Máthé et al 2014 ; Park et al 2016 ; Zhong et al 2015 ). On the other hand, one of the possible microbial community responses to increasing salinity is the replacement of suboptimally adapted taxa by taxa better adapted to the given salinity conditions (Wu et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Marinobacter was proposed by Gauthier et al (1992) with the description of Marinobacter hydrocarbonoclasticus as the type species. At the time of writing, the genus Marinobacter comprises 37 species with validly published names ( http://www.bacterio.net/marinobacter.html ; Parte, 2014; Vaidya et al , 2015; Zhong et al , 2015). Phylogenetic analysis based on 16S rRNA gene sequences showed that the genus Marinobacter falls within the class Gammaproteobacteria (Anzai et al , 2000).…”
mentioning
confidence: 99%
“…Phylogenetic analysis based on 16S rRNA gene sequences showed that the genus Marinobacter falls within the class Gammaproteobacteria (Anzai et al , 2000). Members of the genus Marinobacter have been isolated from a variety of marine environments (Zhong et al , 2015). During recent screening of novel bacteria from the junction between the ocean and a freshwater lake on the East Sea of South Korea, many novel bacterial strains have been isolated and characterized taxonomically.…”
mentioning
confidence: 99%